2021
DOI: 10.30867/action.v6i1.391
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan peer group support, uang saku dan pola konsumsi pangan dengan status gizi lebih pada remaja

Abstract: The problem of overweight in adolescents is caused by multiplicity, including friendships and also the amount of pocket money which will affect the pattern of daily food consumption. The purpose of this study was to analyze the relationship peer group support, pocket money, and food consumption patterns with overweight. This research is observational with a cross-sectional approach. The sample was selected by 50 respondents with stratified random sampling technique, this study was conduction in 2020. Data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
7
0
3
Order By: Relevance
“…This selection is also in accordance with previous research which showed that urban areas of residence were associated with increasing expenditure and participation in the consumption of SSBs or sweetened drinks (11). Then referring to the preliminary data in previous research, there are 32% of students are overweight at 47 Jakarta Senior High School (12). The results of this study are expected to increase knowledge about the consumption of SSBs so that it is expected that there can be a decrease in excessive consumption of SSBs and can prevent negative impacts on health.…”
Section: Introductionsupporting
confidence: 84%
“…This selection is also in accordance with previous research which showed that urban areas of residence were associated with increasing expenditure and participation in the consumption of SSBs or sweetened drinks (11). Then referring to the preliminary data in previous research, there are 32% of students are overweight at 47 Jakarta Senior High School (12). The results of this study are expected to increase knowledge about the consumption of SSBs so that it is expected that there can be a decrease in excessive consumption of SSBs and can prevent negative impacts on health.…”
Section: Introductionsupporting
confidence: 84%
“…The data showed that The average pocket money for female students was around Rp 500,000 -Rp 1,000,000. The results of research by Rahman stated that there was a relationship between pocket money and food consumption patterns and nutritional status 24 . Furthermore, Miao Li also stated that pocket money was related to consuming unhealthy food and being overweight 25 .…”
Section: Resultsmentioning
confidence: 99%
“…This means that when a person's energy intake is high, it can increase his body fat percentage [42]. In addition, a study by Rahman et al [13], also found a link between fat intake and percent body fat. Consumption of sufficient fat can prevent excess fat from accumulating in the body which can increase body fat percentage.…”
Section: Relationship Between Diet and Nutritional Status Of Adolesce...mentioning
confidence: 95%
“…Meanwhile, according to Sugiatmi and Handayani (2018), overnutrition status is the accumulation of excess body fat, which can cause various types of non-communicable diseases. More nutritional status can occur in many different groups, especially in adolescents [13]. Some of the factors that contribute to obesity include food intake and physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation